Parade : 2023 Broadway cast recording [compact disc] - Brown, Jason Robert; Uhry, Alfred (Immersive Music/Interscope Records, 2023)
Parade is a musical with a book by Alfred Uhry and music and lyrics by Jason Robert Brown. The musical is a dramatization of the 1913 trial and imprisonment, and 1915 lynching, of Jewish American Leo Frank in Georgia.